Building classroom discipline - Charles, C. M.; Senter, Gail W. (Boston : Pearson/Allyn and Bacon, 2008)
The leading text in the field, this book analyzes the contributions of the leading authorities in discipline to show how their theories and systems can be used by teachers to create structures of positive discipline. The text analyzes 18 models of school discipline developed by educational thinkers over the past 60 years and shows how they can be applied in realistic situations. A unique contribution of the text is that the present-day theorists listed also coordinate with Professor Charles to ensure accuracy in the presentation of their models. Teachers are motivated to create a structure of positive discipline based on the most effective elements from traditional and current disciplinary approaches.
Includes bibliographical references and index.
Keywords: School discipline; Classroom management